Analisis Location Quotient dalam Penentuan Potensi Sektor Ekonomi di Kota Malang - Gheareta Nugraheni (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This research was conducted Malang city with the aim of knowing and analyzing the basic and non-base sectors, the performance of the economic sector and to find out the potential sectors in the city of Malang. This type of quantitative descriptive research. The data used is time series data, namely PDRB data for Malang City from 2018 to 2022 which are analyzed using three analytical tools, namely Location Quotient and Dynamic Location Quotient (LQ and DLQ), Shift Share (SS), and Klassen Typology. The results of LQ and DLQ analysis show that the base sector is the construction sector and the corporate services sector. Shift share analysis shows the performance of each sector in Malang City that the wholesale and retail trade sector has the highest growth compared to growth in East Java. The agricultural sector, the mining sector, the gas electricity procurement sector, the construction sector, the transportation and warehousing sector, the corporate services sector, and the health services sector are sectors that have high regional competitive advantages. The results of the Klassen typology analysis show that only the electricity and gas procurement sector is classified as an advanced and fast-growing sector.